(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Anti-mullerian hormone (AMH) in largely expressed throughout folliculogenisis (by granulosa cells in ovarian follicles) but highest in pre-antral and small antral steges (<4mm) drameter of development. Objective: To analyse the usefulness of plasma anti-mullerian hormone (AMH) measurement as a test for assessing ovarian reserve in Polycystic ovary syndrome with sub fertility, Methodology: Women with PCOS and sub fertility, were included in this study with age group 18-35yrs. This Prospetive cohort study done in 30 cases in ShSMC with purposive randomized sampling, from January 2015 to December 2015. Serum, plasma & for evaluation of PCOS, preferably TV-USG was done. Result: In this study we analyze 30 serum samples from patient aged between 18-35 years and transvaginal ultrasonography was done simultaneously. Mean age group of my patient was 25.2±4.7 years which correlates with AMH level in PCOS which is statistically significant (p<0.001). Mean level of AMH is 5.7±4.9 mg/ml which is also correlate with transvaginal USG scan with the feature of PCOS (p<.0.001). More than 50% woman presents with features of subfertility with PCOS and 46.7% are normal ovaries. Mean menstrual day 7.6 (4-12 days) which have a good linear correlation with irregularities of menstrual cycle and PCOS (p<0.05). Conclusion: To conclude AMH appears to have a major inhibiting role during folliculogenesis, which may contribute to anovulation in PCOS. The reason for the raised AMH in PCOS may give clues as to the mechanism os anovulation. J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 3-5